Virological failure of first-line antiretroviral therapy in children living with HIV in Indonesia and associated factors - Nia Kurniati; Zakiudin Munasir; Pramita Gayatri; Evy Yunihastuti; Budiman Bela; Anggraini Alam (Indonesian Pediatric Society, 2022)
Background The World Health Organization (WHO) recommends viral load (VL) monitoring for HIV patients on antiretroviral therapy (ART). However, availability of VL monitoring in low-income countries remains limited. Objective To investigate factors associated with virological failure in HIV-infected children treated without routine VL monitoring. Methods This cohort study was done in children living with HIV (CLHIV) registered at Cipto Mangunkusumo General Hospital from 2004 to 2021. Viral load monitoring was not routinely done. Subjects with at least one VL result after 6 months on ART were included in the study. Virological failure was defined as a VL of >1,000 copies. Subjects’ data were obtained from medical records, laboratory reports, and dispensing pharmacies. Statistical analysis was done following survival analysis with hazard ratio. Results There were 384 children who had at least 1 VL result after ART was initiated. Median age at diagnosis was 30 months. Length of follow-up ranged from 6 to 216 months, with a mean frequency of VL monitoring of 0.7 times/person/year. Most subjects were already in clinical stages 3 and 4 (77.8%); 75% met severe immunodeficiency criteria. Virological failure was found in 45.8% of subjects after a median of 33 months on first-line ART, yielding an incidence of 3.3 per 1,000 person months. Independent associated factors were age at diagnosis of <60 months (HR 1.714; 95%CI 1.13 to 2.6), severe immunodeficiency (HR 1.71; 95%CI 1.15 to 2.54), referral cases (HR 1.70; 95%CI 1.23 to 2.36), and WHO clinical staging 3 (HR 1.987; 95%CI 0.995 to 3.969) and 4 (HR 2.084; 95%CI 1.034 to 4.201). Subjects with virological failure had lower weight-for-age z-scores [median 1.92; interquartile range (IQR) -3.003 to -0.81] and height-for-age z-scores [median -2.05; IQR -2.902 to -1.04] at the time of failure. Conclusions In HIV-infected children treated without routine VL monitoring, age at diagnosis <60 months, severe immunodeficiency, WHO clinical stage 3 and 4, and referral from other centers were associated with virological failure.